Comprendre le risque routier professionnel par l’analyse de l’activité : l’exemple des conducteurs de travaux - Justine Forrierre; Francis Six (Perspectives Interdisciplinaires sur le Travail et la Santé)
This paper presents the results of a study on the occupational road risk of workers for whom driving is not their job but who drive frequently: Public Works site supervisors. Using the activity’s theoretical framework, we show that in order to understand and prevent this risk, the work activity needs to be known and understood. In fact, driving is a work activity and the related risk is an occupational risk. To prevent the latter, it is necessary to go beyond the simple behavioural driving activity approach and consider all the determinants of the work activity that cause the work supervisor to drive and take risks on the road. We note that the organizational aspect (requirements, organization of production, human resources policy), the material aspect (vehicle, communication tools) and the relations between the companies (customer-relational) have an impact on the driving activity and that the prevention of road risk therefore requires an overall approach (individual, collective, in the company, and with other companies) that involves these different areas.